Near telomere-to-telomere genome assemblies of Silkie Gallus gallus and Mallard Anas platyrhynchos restored the structure of chromosomes and “missing” genes in birds - Qiangsen Zhao; Zhongtao Yin; Zhuocheng Hou (Journal of Animal Science and Biotechnology)
Abstract Background Chickens and ducks are vital sources of animal protein for humans. Recent pangenome studies suggest that a single genome is insufficient to represent the genetic information of a species, highlighting the need for more comprehensive genomes. The bird genome has more than tens of microchromosomes, but comparative genomics, annotations, and the discovery of variations are hindered by inadequate telomere-to-telomere level assemblies. We aim to complete the chicken and duck genomes, recover missing genes, and reveal common and unique chromosomal features between birds. Results The near telomere-to-telomere genomes of Silkie Gallus gallus and Mallard Anas platyrhynchos were successfully assembled via multiple high-coverage complementary technologies, with quality values of 36.65 and 44.17 for Silkie and Mallard, respectively; and BUSCO scores of 96.55% and 96.97% for Silkie and Mallard, respectively; the mapping rates reached over 99.52% for both assembled genomes, these evaluation results ensured high completeness and accuracy. We successfully annotated 20,253 and 19,621 protein-coding genes for Silkie and Mallard, respectively, and assembled gap-free sex chromosomes in Mallard for the first time. Comparative analysis revealed that microchromosomes differ from macrochromosomes in terms of GC content, repetitive sequence abundance, gene density, and levels of 5mC methylation. Different types of arrangements of centromeric repeat sequence centromeres exist in both Silkie and the Mallard genomes, with Mallard centromeres being invaded by CR1. The highly heterochromatic W chromosome, which serves as a refuge for ERVs, contains disproportionately long ERVs. Both Silkie and the Mallard genomes presented relatively high 5mC methylation levels on sex chromosomes and microchromosomes, and the telomeres and centromeres presented significantly higher 5mC methylation levels than the whole genome. Finally, we recovered 325 missing genes via our new genomes and annotated TNFA in Mallard for the first time, revealing conserved protein structures and tissue-specific expression. Conclusions The near telomere-to-telomere assemblies in Mallard and Silkie, with the first gap-free sex chromosomes in ducks, significantly enhanced our understanding of genetic structures in birds, specifically highlighting the distinctive chromosome features between the chicken and duck genomes. This foundational work also provides a series of newly identified missing genes for further investigation.